Set adrift: Capitalist transformations and community politics along mumbai`s shore - Nair, Gayatri (New Delhi Oxford University Press, 2021)
The Koli community in Mumbai-which has been practising fishing for centuries-has experienced rapid changes over the last few decades, in the forms of increased mechanization, export of fish to global markets, and the pressure of urbanization on their living and work spaces. The capitalist transformation in fishing has altered what was once a caste-based practice to one that brought to it investors from outside the community, migrant workers, and ecological degradation.